PENGARUH CARA APLIKASI DAN DOSIS PUPUK KANDANG PADA PERTUMBUHAN DAN HASIL TANAMAN NILAM - Sugiatno, Sugiatno (JURNAL AGROTROPIKA, 2013)
The problem in patchouli plant cultivation is the reduction of soil?s fertility level which effects on the decreasing of plant growth and yield. Application of cattle manure is a key to increase the soil?s productivity. The objective of this research is to study the effect of application method and cattle manure dosage on plant growth and yield of patchouli plant. This research was conducted at Lampung Agriculture Polytechnic research?s field in Hajimena Bandar Lampung from December 2010 to March 2011. The experiment was factorial designed (2 X 4 factors) with randomized completely block design with three replications. The first factor was manure cattle application method: spreaded on soil surface or mixed with top soil. The second factor was manure cattle dosage, consist of 0, 10, 20, and 30 ton/ha. Result showed that (1) the application of manure cattle increased the growth and yield of patchouli plant; the increasing of the dosage would increase plant growth and yield of patchouli plant, (2) Patchouli plant which applied with cattle manure that mixed with top soil has longer primary root, (3) There is no interaction effect between application method and manure cattle dosage on plant growth and yield of patchouli plant. Key words: application method, cattle manure, growth, yield, Pogostemon cablin